Pushing the Band Gap Envelope of Quasi-Type II Heterostructured Nanocrystals to Blue: ZnSe/ZnSe1-XTeX/ZnSe Spherical Quantum Wells - Jun Hyuk Chang; Hak June Lee; Seunghyun Rhee; Donghyo Hahm; Byeong Guk Jeong; Gabriel Nagamine; Lazaro A. Padilha; Kookheon Char; Euyheon Hwang; Wan Ki Bae (Energy material advances, 2021)
Quasi-type II heterostructured nanocrystals (NCs) have been of particular interest due to their great potential for controlling the interplay of charge carriers. However, the lack of material choices for quasi-type II NCs restricts the accessible emission wavelength from red to near-infrared (NIR), which hinders their use in light-emitting applications that demand a wide range of visible colors. Herein, we demonstrate a new class of quasi-type II nanoemitters formulated in ZnSe/ZnSe1-XTeX/ZnSe seed/spherical quantum well/shell heterostructures (SQWs) whose emission wavelength ranges from blue to orange. In a given geometry, ZnSe1-XTeX emissive layers grown between the ZnSe seed and the shell layer are strained to fit into the surrounding media, and thus, the lattice mismatch between ZnSe1-XTeX and ZnSe is effectively alleviated. In addition, composition of the ZnSe1-XTeX emissive layer and the dimension of the ZnSe shell layer are engineered to tailor the distribution and energy of electron and hole wave functions. Benefitting from the capabilities to tune the charge carriers on demand and to form defect-free heterojunctions, ZnSe/ZnSe1-XTeX/ZnSe/ZnS NCs show near-unity photoluminescence quantum yield (PL QY>90%) in a broad range of emission wavelengths (peak PL from 450 nm to 600 nm). Finally, we exemplify dichromatic white NC-based light-emitting diodes (NC-LEDs) employing the mixed layer of blue- and yellow-emitting ZnSe/ZnSe1-XTeX/ZnSe/ZnS SQW NCs.